x = 1 ∑ ∞ 5 x − 1 5 4 x 2 ( − 1 ) x + 1 = ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Consider the infinite series x = 1 ∑ ∞ a x = 1 − a a for ∣ a ∣ < 1 .
Differentiating with respect to a gives
x = 1 ∑ ∞ x ⋅ a x − 1 = ( 1 − a ) 2 1 .
Multiplying it by a , we have
x = 1 ∑ ∞ x ⋅ a x = ( 1 − a ) 2 a .
Differentiating with respect to a again gives
x = 1 ∑ ∞ x 2 ⋅ a x − 1 = ( 1 − a ) 3 a + 1 .
Multiplying it by a , we have
x = 1 ∑ ∞ x 2 ⋅ a x − 1 = ( 1 − a ) 3 a ( a + 1 ) .
The series in question is equal to ( 5 4 ⋅ 5 ⋅ − 1 ) x = 1 ∑ ∞ x 2 a x , where a = − 5 1 . Upon substitution, we have the answer of 2 5 .
Exactly the same approach!!!
Log in to reply
Here's another way to solve this:
x 2 = x ( x − 1 ) + x .
The series in question can be expressed as B ( x = 1 ∑ ∞ x ( x − 1 ) a x − 2 ) + C ⋅ ( x = 1 ∑ ∞ x a x − 1 ) for constants B and C to be determined.
Can you figure out the rest?
Problem Loading...
Note Loading...
Set Loading...
Consider the summation:
S 5 S S + 5 S 5 1 ( S + 5 S ) ( S + 5 S ) + 5 1 ( S + 5 S ) ⟹ 2 5 3 6 S S k = 1 ∑ ∞ 5 k − 1 5 4 ( − 1 ) k + 1 k 2 = k = 1 ∑ ∞ 5 k − 1 ( − 1 ) k + 1 k 2 = 1 − 5 4 + 5 2 9 − 5 3 1 6 + 5 4 2 5 − ⋯ = 5 1 − 5 2 4 + 5 3 9 − 5 4 1 6 + 5 5 2 5 − ⋯ = 1 − 5 3 + 5 2 5 − 5 3 7 + 5 4 9 − ⋯ = 5 1 − 5 2 3 + 5 3 5 − 5 4 7 + 5 5 9 − ⋯ = 1 − 5 2 + 5 2 2 − 5 3 2 + 5 4 2 − ⋯ = 1 − 5 2 ( 1 + 5 1 1 ) = 3 2 = 5 4 2 5 = 5 4 S = 2 5